PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN DI PT. CAPRIFARMINDO LABORATORIES VETERINARY VACCINE PLANT - Romadhona, Fitria; Recky, Recky; Ali, Mochammad Mukti (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
This study aims to analyze the influence of work motivation, work environment, and job satisfaction on employees' turnover intention at PT. Caprifarmindo Laboratories Veterinary Vaccine Plant. Turnover intention is a critical issue in human resource management, especially in the pharmaceutical industry, where workforce stability significantly impacts operational efficiency. This research employs a quantitative approach using a survey method, involving 70 employee respondents as the sample, selected through proportional random sampling techniques. The findings indicate that efforts to enhance work motivation and job satisfaction can serve as effective strategies to reduce turnover intention. Therefore, the company is recommended to develop programs that foster employees' intrinsic motivation and ensure job satisfaction through fair management policies, competitive compensation, and clear career development pathways. Keywords: